Kajian Komparatif Sistem Among dan Metode Montessori - Rohmatu, Habibah Pidi; Awaliyah, Siti; Sukriono, Didik (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This article aims to discuss the similarities and differences in the systems of thinking among and the Montessori method. This study uses a historical-comparative research approach. The results obtained are the basic equations of the system among and Montessori regarding the concept of education for an independent spirit and access to education for people from various socio-economic strata. The background for the formulation of the Among system is to achieve Indonesian independence through education. Montessori created a method of renewing education for Rome’s poorest children. The difference between the two is a classical concept. The among system uses a classical system like schools in general with the same methods, materials, and activities carried out by children. The Montessori method makes the class just a gathering place, children are free to carry out various activities according to their interests. The among system is developed for children, adolescents, and adults to train their senses and play their own children. The Montessori method was developed for early childhood education, which is more concerned with the development of the senses.